2010
DOI: 10.1021/ja102718x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Reversal of Enantioselectivity in the Proline-Mediated α-Amination of Aldehydes Induced by Tertiary Amine Additives

Abstract: The renaissance in organocatalysis that was sparked by the List, Lerner, and Barbas 1 study of the proline-mediated aldol reaction has led to reports of a wide variety of electrophile/ nucleophile reactions catalyzed by a range of primary and secondary amines. 2 In addition to its efficiency in the archetypal aldol reaction, proline has also been shown to be effective in other enantioselective transformations thought to proceed via an enamine mechanism, including Mannich reactions, enamine addition to azo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
0
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 21 publications
4
47
0
9
Order By: Relevance
“…Zusammen mit den Ergebnissen der Gruppen von Blackmond und Armstrong [4] stützen diese Daten die Annahme, dass im stereogenen Schritt von prolinkatalysierten Reaktionen die Bildung von Oxazolidinonen möglich ist, [3] vor allem wenn starke Basen zugegen sind. Unsere Ergebnisse tangieren nicht die Deutung der Stereoselektivitäten einer Vielzahl prolinkatalysierter Reaktionen durch ÜZ-A, wenn das effektive Nucleophil eine Enamincarbonsäure [1e, 20] und nicht ein Enamincarboxylat-Ion ist.…”
Section: Nucleophilunclassified
See 2 more Smart Citations
“…Zusammen mit den Ergebnissen der Gruppen von Blackmond und Armstrong [4] stützen diese Daten die Annahme, dass im stereogenen Schritt von prolinkatalysierten Reaktionen die Bildung von Oxazolidinonen möglich ist, [3] vor allem wenn starke Basen zugegen sind. Unsere Ergebnisse tangieren nicht die Deutung der Stereoselektivitäten einer Vielzahl prolinkatalysierter Reaktionen durch ÜZ-A, wenn das effektive Nucleophil eine Enamincarbonsäure [1e, 20] und nicht ein Enamincarboxylat-Ion ist.…”
Section: Nucleophilunclassified
“…[4] Diese Umkehr wurde durch einen Wechsel von ÜZ-A zu ÜZ-C bei Anwesenheit tertiärer Amine erklärt, wobei der Angriff des Elektrophils am s-trans-Isomer des Enamincarboxylats I-2 erfolgt. Die Funktion der Carboxylatgruppe konnte jedoch nicht geklärt werden; sie soll entweder als sterisch abschirmende Gruppe wirken oder in Übereinstim-mung mit Seebach, Eschenmoser et al am Additionsschritt beteiligt sein.…”
unclassified
See 1 more Smart Citation
“…In order to account for the observed stereoselectivities, it was assumed that TS-B (Scheme 1), which yields the more stable oxazolidinone, is favored over the stereoelectronically preferred TS-C. [3] Support for the involvement of the enamine carboxylate I-2 has recently been provided by Blackmond, Armstrong et al, who reported that the enantioselectivity of prolinecatalyzed reactions of aliphatic aldehydes with azodicarboxylates is reversed in the presence of tertiary amines. [4] This reversal was explained by a change from TS-A to TS-C in the presence of amines, where the attack of the electrophile occurs at the s-trans isomer of the enamine carboxylate. The role of the carboxylate group could not be clarified, however, and it was suggested that CO 2 À either acts as a steric blocking group, or in accordance with Seebach, Eschenmoser et al, participates in the addition step.…”
mentioning
confidence: 99%
“…The role of the carboxylate group could not be clarified, however, and it was suggested that CO 2 À either acts as a steric blocking group, or in accordance with Seebach, Eschenmoser et al, participates in the addition step. [4] Traditionally, anchimeric assistance (neighboring-group participation) has been derived from stereochemical as well as kinetic investigations in a variety of reactions, e.g., solvolytic displacement reactions, electrophilic additions, and eliminations. [5] Owing to the conformational flexibility of the intermediate enamines stereochemical investigations did not provide unequivocal evidence for or against the formation of oxazolidinones in the stereogenic step.…”
mentioning
confidence: 99%